Islamic Community Empowerment Based on Piil Pesenggiri in Preserving Islamic Cultural Values in Teluk Betung, Bandar Lampung: A Study of the Marga Balak of Coastal Lampung in Negeri Olok Gading Subdistrict - Imam Mahali; Idham Chalid; Faizal; M. Mawardi; Rini Setiawati (GoAcademica Research & Publishing, 2026)
This study examines the integration of coastal Lampung customary values with Islamic teachings in fostering social harmony in Negeri Olok Gading Subdistrict, Bandar Lampung. Employing a qualitative approach, the findings reveal that traditional structures such as Kebandaran, title bestowal (Adok), as well as communal traditions like tahlilan and nughun, continue to be preserved without exhibiting a dichotomy between custom and religion. Instead, customary practices function as a cultural medium for the transmission of Islamic values. Traditional leaders, including Pangeran and Punyimbang, play a pivotal role in promoting religious moderation and maintaining a balance between tradition and Islamic law. This study proposes an integrative model through the concept of Islamic Community Development and Empowerment (ICDE), grounded in the principles of justice, participation, and mutual assistance. Guided by the framework of Maqasid al-Shari’ah, this empowerment model emphasizes the protection of five essential dimensions religion, life, intellect, wealth, and lineage through the hierarchical priorities of dharuriyyat, hajiyyat, and tahsiniyyat. The al-‘urf methodology is employed to legitimize established societal customs as a basis for normative guidance, while the indigenization of Islam ensures the contextual realization of Qur’anic values within local cultural frameworks, in accordance with the legal maxim al-‘adah muhakkamah. The findings further demonstrate that the philosophy of Piil Pesenggiri encompassing the values of Bejuluk Adok, Nemui Nyimah, Nengah Nyapur, and Sakai Sembaian is philosophically aligned with Islamic principles such as muru’ah (dignity), silaturahmi (social bonding), ukhuwah (brotherhood), and ta‘awun (mutual cooperation). The proposed empowerment strategy includes strengthening spiritual, intellectual, and cultural capacities, exemplified by the establishment of the Sanggar Kebandaran Marga Balak as an initiative to preserve local wisdom and foster a harmonious, contextual, and inclusive religious life within a pluralistic society.